Composite solid electrolyte and preparation method and application thereof
Patent Information
- Application Number
- CN202611200065.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-30
AI Technical Summary
然而,现有复合体系仍面临以下关键挑战:其一,无机填料的引入未能有效改善聚合物电解质的室温离子传导性能
(1)本发明通过磷酸钛锂与单宁酸改性滑石粉的协同复配,构建了“点-面”结合的高效离子传输网络。其中,磷酸钛锂作为快离子导体嵌入聚合物电解质基体中,提供连续的体相锂离子快速传输通道,有效弥补了聚合物电解质室温离子电导率低的缺陷;单宁酸改性滑石粉则起到活化界面的作用,其表面的酚羟基极性基团能够与锂盐阴离子发生强相互作用,促进锂盐在聚合物电解质中的充分解离并固定阴离子,从而显著提高锂离子迁移数、降低浓差极化,使复合固态电解质兼具高离子电导率和高锂离子迁移数的双重优势。
Smart Images

Figure CN123018094A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid electrolyte technology, specifically relating to a composite solid electrolyte, its preparation method, and its application. Background Technology
[0002] Solid-state lithium batteries are widely considered a key development direction for next-generation energy storage technology due to their high energy density and excellent safety. As a core component, the performance of the solid electrolyte directly determines the overall performance of the battery. Currently, solid electrolytes are mainly divided into two categories: inorganic solid electrolytes and polymer solid electrolytes. NASICON-type inorganic solid electrolytes, represented by lithium titanium phosphate (LTP), have high bulk ionic conductivity, but their large grain boundary resistance, poor interfacial contact with electrodes, and high rigidity and brittleness severely limit their practical applications. On the other hand, although polymer solid electrolytes possess good flexibility and good interfacial contact performance, their room temperature ionic conductivity is low (typically below 10). -5 Its low S / cm and low lithium-ion transference number (typically below 0.5) make it difficult to meet the requirements for high power density.
[0003] Combining the advantages of both types of materials, the strategy of introducing inorganic fillers into polymer matrices to construct composite solid-state electrolytes has been widely studied. However, existing composite systems still face the following key challenges: First, the introduction of inorganic fillers has failed to effectively improve the room-temperature ion conductivity of polymer electrolytes. In conventional solution mixing processes, inorganic fillers mostly exist in the polymer matrix as inert dispersed phases, making it difficult to form effective synergistic effects with the matrix and lithium salt, thus failing to construct continuous and efficient lithium-ion transport channels, resulting in limited improvement in the room-temperature ion conductivity of the composite electrolyte. Second, the lithium salt dissociation in the composite system is insufficient, and the concentration polarization problem caused by anion migration has not been effectively solved. Traditional inorganic fillers lack the ability to specifically anchor lithium salt anions, allowing a large number of anions to migrate freely, resulting in a low lithium-ion transference number. This leads to increased polarization under high-current charge-discharge conditions, limiting the rate performance of solid-state batteries. Third, simple physical mixing of inorganic fillers and polymer matrices makes it difficult to achieve effective chemical stability control at the electrode / electrolyte interface. The decomposition side reactions of polymer electrolytes under high voltage are not sufficiently suppressed, the electrochemical stability window is limited, and the interfacial impedance continues to increase with cycling, resulting in poor cycle stability of solid-state batteries. Summary of the Invention
[0004] To address the above problems, the purpose of this invention is to provide a composite solid electrolyte, its preparation method, and its applications.
[0005] In a first aspect, the present invention provides a composite solid electrolyte comprising, by mass fraction: 10-15 parts of a composite material composed of lithium titanium phosphate and modified talc, 15-30 parts of lithium salt, and 15-20 parts of polymer electrolyte; wherein: the modified talc is tannic acid modified talc, and the mass ratio of lithium titanium phosphate to modified talc is 1:(0.3-0.5).
[0006] Secondly, the present invention provides a method for preparing a composite solid electrolyte, comprising the following steps: A composite material consisting of lithium titanium phosphate and modified talc, lithium salt, and polymer electrolyte are mixed and dispersed in a solvent to obtain a slurry. The slurry is then cast into a film and subjected to gradient drying to obtain a composite solid electrolyte.
[0007] Thirdly, the present invention provides a solid-state battery, including the aforementioned composite solid-state electrolyte.
[0008] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: (1) This invention constructs a highly efficient ion transport network combining "point-surface" by synergistic compounding of lithium titanium phosphate and tannic acid-modified talc. Among them, lithium titanium phosphate, as a fast ion conductor, is embedded in the polymer electrolyte matrix to provide a continuous bulk lithium ion fast transport channel, effectively compensating for the low room temperature ionic conductivity of polymer electrolyte; tannic acid-modified talc plays the role of activating the interface, and its surface phenolic hydroxyl polar groups can interact strongly with lithium salt anions, promoting the full dissociation of lithium salt in polymer electrolyte and fixing anions, thereby significantly improving lithium ion transport number and reducing concentration polarization, so that the composite solid electrolyte has the dual advantages of high ionic conductivity and high lithium ion transport number.
[0009] (2) This invention achieves complementary reinforcement of the rigid and flexible solid electrolyte through the synergistic effect of the rigid filling of talc powder and the flexible bridging of tannic acid. Talc powder, as an inorganic rigid filler, is uniformly dispersed in the polymer electrolyte matrix, which can provide effective structural support for the electrolyte membrane. Tannic acid, as a natural polyphenol, is rich in phenolic hydroxyl groups and has strong adhesion. It can be used as a flexible bridging agent to improve the interfacial compatibility between the inorganic filler and the polymer electrolyte matrix, alleviate the problem of increased brittleness caused by the addition of inorganic filler alone, and make the prepared electrolyte membrane have good flexibility while maintaining a certain rigidity. This helps to maintain structural integrity during repeated charging and discharging and extend the cycle life of the battery. Attached Figure Description
[0010] Figure 1 The image shows a SEM image of the composite material consisting of lithium titanium phosphate and modified talc prepared in Example 1.
[0011] Figure 2 The image shows the constant current charge-discharge cycle test results of the Li-Li symmetric battery assembled with the composite solid electrolyte prepared in Example 1.
[0012] Figure 3 The constant current charge-discharge cycle test results of the Li-Li symmetric battery assembled with the composite solid electrolyte prepared in Comparative Example 1 are shown.
[0013] Figure 4 The constant current charge-discharge cycle test results of the Li-Li symmetric battery assembled with the composite solid electrolyte prepared in Comparative Example 2 are shown.
[0014] Figure 5 The constant current charge-discharge cycle test results of the Li-Li symmetric battery assembled with the composite solid electrolyte prepared in Comparative Example 3 are shown. Detailed Implementation
[0015] To facilitate understanding of the present invention, the present invention will be described more fully and in detail below with reference to the accompanying drawings and preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.
[0016] As mentioned above, in a first aspect, the present invention provides a composite solid electrolyte, comprising, by mass fraction: A composite material consisting of lithium titanium phosphate and modified talc, in quantities of 10 to 15 parts, including but not limited to: 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, etc. Lithium salt 15-30 parts, including but not limited to: 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, etc.; Polymer electrolyte 15-20 parts; including but not limited to: 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc.; Among them, the modified talc is tannic acid modified talc, and the mass ratio of lithium titanium phosphate to modified talc is 1:(0.3~0.5), including but not limited to: 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, etc.
[0017] This invention uses a composite material composed of lithium titanium phosphate and tannic acid-modified talc as the core functional component to construct a highly efficient ion transport network combining "point" and "surface": lithium titanium phosphate, as a fast ion conductor, plays the role of "point," providing a rapid bulk lithium-ion transport channel to compensate for the low room temperature conductivity of polymer electrolytes; tannic acid-modified talc plays the role of "surface," with its surface-grafted phenolic hydroxyl polar groups strongly interacting with lithium salt anions, promoting lithium salt dissociation and anchoring anions, and suppressing concentration polarization, thereby achieving both high ion conductivity and high lithium-ion transport number.
[0018] Meanwhile, the composite material composed of modified talc and lithium titanium phosphate is uniformly dispersed in the polymer matrix as an inorganic rigid filler to provide structural support for the electrolyte membrane, ensure the mechanical strength of the electrolyte, and resist lithium dendrite puncture. Tannic acid, as a flexible bridging agent, can form a hydrogen bond network with the F atoms in the polyvinylidene fluoride molecular chain through its phenolic hydroxyl groups, improve the compatibility of the inorganic-organic interface, avoid brittle fracture caused by agglomeration, and enable the electrolyte membrane to have both high modulus and good flexibility, maintaining structural integrity during cycling.
[0019] This invention achieves multiple layers of stable protection at the electrode / electrolyte interface through the synergistic effect of the chemical film-forming action of the phenolic hydroxyl groups in tannic acid and the physical barrier effect of the inorganic filler. Specifically, the abundant phenolic hydroxyl groups in tannic acid molecules possess high electrochemical activity, enabling preferential redox reactions at the electrode / electrolyte interface to generate a dense interfacial protective film rich in inorganic components such as Li₂O and LiF in situ. This interfacial film, on the one hand, broadens the electrochemical stability window of the composite solid-state electrolyte, effectively suppressing the decomposition side reactions of the polymer matrix under high voltage; on the other hand, it reduces the interfacial contact impedance between the electrode and the electrolyte, decreasing interfacial polarization, thereby significantly improving the cycle stability of the solid-state battery.
[0020] In some embodiments, the method for preparing the composite material composed of lithium titanium phosphate and modified talc includes the following steps: ball milling and mixing lithium titanium phosphate and modified talc, followed by drying, to obtain the final product.
[0021] Pre-ball milling and compounding lithium titanium phosphate with modified talc allows for thorough dispersion and close contact at the micro-nano scale, ensuring microscopic pre-coupling between the bulk lithium-ion transport channels provided by lithium titanium phosphate and the polar active sites on the surface of modified talc. The tannin phenolic hydroxyl groups in the modified talc strongly interact with lithium salt anions, while its surface functional groups form interfacial bonds with polymer electrolyte molecular chains. This constructs an active transition interface on the surface of lithium titanium phosphate particles, combining anion anchoring and polymer affinity, facilitating the extraction of lithium ions from the bulk lithium titanium phosphate phase. After extraction, the lithium ions are efficiently transferred to the polymer electrolyte matrix through the active interface, forming a continuous, low-barrier lithium ion transport path from the inorganic fast ion conductor through the functionalized filler interface to the polymer matrix. In addition, the tannic acid polar groups on the surface of the modified talc can be adsorbed on the surface of lithium titanium phosphate particles, effectively inhibiting the aggregation of lithium titanium phosphate and improving its interfacial compatibility with the polymer electrolyte. This avoids phase separation and interfacial defects caused by polarity differences during direct blending, thereby maintaining the uniform dispersion of each component and the stability of the interfacial structure in the subsequent film formation, laying the structural foundation for improving the overall performance of the solid electrolyte.
[0022] In some embodiments, the ball milling is performed using wet ball milling, and the medium for wet ball milling is ethanol.
[0023] In some embodiments, the mass ratio of lithium titanium phosphate to the medium is 1:(3~5), including but not limited to: 1:3, 1:3.5, 1:4, 1:4.5, 1:5, etc.
[0024] In some embodiments, the ball milling mixing time is 2-3 hours, including but not limited to: 2 hours, 2.5 hours, and 3 hours; the drying temperature is 100-120°C, including but not limited to: 100°C, 105°C, 110°C, 115°C, and 120°C; and the drying time is 12-18 hours, including but not limited to: 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, and 18 hours.
[0025] In some embodiments, the method for preparing tannic acid-modified talc includes the following steps: adding tannic acid and talc to a solvent and stirring to react, thereby obtaining tannic acid-modified talc.
[0026] In some embodiments, the mass ratio of tannic acid to talc is (0.01~0.03):1, including but not limited to: 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.03:1, etc.; the mass ratio of talc to solvent is 1:(300~500), including but not limited to: 1:300, 1:350, 1:400, 1:450, 1:500, etc., and the solvent is water.
[0027] In some embodiments, the stirring reaction time is 10-15 hours, including but not limited to: 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, etc.
[0028] In some embodiments, after the stirring reaction is completed, the mixture is filtered, washed, and dried sequentially to obtain tannic acid modified talc powder; wherein: the drying temperature is 100~120℃, including but not limited to: 100℃, 105℃, 110℃, 115℃, 120℃, etc.; the drying time is 3~5h, including but not limited to: 3h, 3.5h, 4h, 4.5h, 5h, etc.
[0029] In some embodiments, the lithium salt is selected from one or more of LiBOB (lithium bis(oxalato)borate), LiDFOB (lithium difluorooxalato)borate), LiODFP (lithium difluorobis(oxalato)phosphate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiBF4 (lithium tetrafluoroborate), and LiPF6 (lithium hexafluorophosphate).
[0030] In some embodiments, the polymer electrolyte is selected from one or both of PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene copolymer) and PVDF-CTFE (polyvinylidene fluoride-trifluorochloroethylene copolymer).
[0031] Secondly, the present invention provides a method for preparing a composite solid electrolyte, comprising the following steps: A composite material consisting of lithium titanium phosphate and modified talc, lithium salt, and polymer electrolyte are mixed and dispersed in a solvent to obtain a slurry. The slurry is then cast into a film and subjected to gradient drying to obtain a composite solid electrolyte.
[0032] The preparation process of this invention is simple and efficient. The uniform dispersion of each component can be achieved by ball milling and mixing. Then, a composite solid electrolyte membrane with a dense, uniform and defect-free surface can be obtained by casting and gradient drying, which is suitable for large-scale production and application.
[0033] In some embodiments, the solvent is one or both of NMP (N-methylpyrrolidone) and DMF (N,N-dimethylformamide).
[0034] In some embodiments, the mass ratio of the polymer electrolyte to the solvent is (0.15~0.2):5, including but not limited to: 0.15:5, 0.16:5, 0.17:5, 0.18:5, 0.19:5, 0.2:5, etc.
[0035] In some embodiments, the specific process of gradient drying is as follows: first, dry at room temperature for 18~28h (including but not limited to: 18h, 20h, 22h, 25h, 28h, etc.), and then raise the temperature to 50~70℃ (including but not limited to: 50℃, 55℃, 60℃, 65℃, 70℃, etc.) and dry for 18~28h (including but not limited to: 18h, 20h, 22h, 25h, 28h, etc.).
[0036] In some embodiments, the thickness of the composite solid electrolyte is 90~110μm, including but not limited to: 90μm, 95μm, 100μm, 105μm, 110μm, 115μm, 120μm, etc.
[0037] Thirdly, the present invention provides a solid-state battery, including the aforementioned composite solid-state electrolyte.
[0038] Preparation Example 1 Titanium oxysulfate, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, and lithium chloride were prepared according to a Li:Ti:P molar ratio of 1:2.02:3.05. After being dissolved in deionized water, the pH of the solution was adjusted to 4 with ammonia water. The reaction was carried out at room temperature for 4 hours. After the reaction was completed, the mixture was aged for 6 hours, then filtered, washed, and dried at 150℃ for 10 hours to obtain the lithium titanium phosphate precursor.
[0039] The lithium titanium phosphate precursor was placed in a muffle furnace and sintered at 900℃ for 15 h to obtain lithium titanium phosphate LiTi2(PO4)3.
[0040] Example 1 The composite solid electrolyte in this embodiment, by mass fraction, comprises: 14 parts of a composite material consisting of lithium titanium phosphate and modified talc, 20 parts of LiPF6, and 18 parts of PVDF-HFP. The specific preparation method is as follows: S1. After dissolving tannic acid in water, add talc powder to obtain a reaction solution, wherein the mass ratio of talc powder, tannic acid and water is 1:0.02:400; stir the reaction solution at room temperature for 12 hours, then filter it, wash the filter residue with deionized water 3 times, and then dry it at 110℃ for 4 hours to obtain modified talc powder.
[0041] S2. The lithium titanium phosphate prepared in Preparation Example 1 and the modified talc powder were dispersed in ethanol at a mass ratio of 1:0.4, wherein the mass ratio of lithium titanium phosphate to ethanol was 1:4. After ball milling for 2.5 h, the mixture was dried at 110 °C for 15 h to obtain a composite material composed of lithium titanium phosphate and modified talc powder.
[0042] The composite material consisting of S3, lithium titanium phosphate and modified talc, LiPF6 and PVDF-HFP were dispersed in DMF solution, wherein the mass ratio of DMF to PVDF-HFP was 5:0.18. After uniform dispersion, a slurry was obtained. The slurry was cast onto a glass plate with a thickness of 130 μm and dried at room temperature for 24 h. Then, the temperature was raised to 60 °C and dried for 24 h to obtain a composite solid electrolyte with a thickness of 102 μm.
[0043] The SEM image of the composite material composed of lithium titanium phosphate and modified talc prepared in step S2 of this embodiment is shown below. Figure 1 As shown, the composite material is irregularly crystalline with particles bonded together, making it impossible to distinguish between lithium titanium phosphate and modified talc.
[0044] Comparative Example 1 It is basically the same as Example 1, except that no modified talc is added.
[0045] The composite solid electrolyte in this comparative example, by mass fraction, comprises: 14 parts lithium titanium phosphate, 20 parts LiPF6, and 18 parts PVDF-HFP. The specific preparation method is as follows: Lithium titanium phosphate, LiPF6, and PVDF-HFP were dispersed in a DMF solution, wherein the mass ratio of DMF to PVDF-HFP was 5:0.18. After uniform dispersion, a slurry was obtained. The slurry was cast onto a glass plate with a thickness of 130 μm and dried at room temperature for 24 h. Then, the temperature was raised to 60 °C and dried for another 24 h to obtain a composite solid electrolyte with a thickness of 102 μm.
[0046] Comparative Example 2 It is basically the same as Example 1, except that the modified talc powder is replaced with talc powder.
[0047] The composite solid electrolyte in this comparative example, by mass fraction, comprises: 14 parts of a composite material consisting of lithium titanium phosphate and talc, 20 parts of LiPF6, and 18 parts of PVDF-HFP. The specific preparation method is as follows: S1 is basically the same as step S2 in Example 1, except that modified talc is replaced by talc powder, and a composite material composed of lithium titanium phosphate and talc powder is prepared accordingly.
[0048] S2 is basically the same as step S3 in Example 1, except that the composite material composed of lithium titanium phosphate and modified talc is replaced by a composite material composed of lithium titanium phosphate and talc.
[0049] Comparative Example 3 The composite solid electrolyte in this comparative example, by mass fraction, comprises: 10 parts lithium titanium phosphate, 4 parts modified talc, 20 parts LiPF6, and 18 parts PVDF-HFP. The specific preparation method is as follows: S1, the same as step S1 in Example 1.
[0050] S2, lithium titanium phosphate, modified talc, LiPF6 and PVDF-HFP are dispersed in DMF solution, wherein the mass ratio of DMF to PVDF-HFP is 5:0.18. After uniform dispersion, a slurry is obtained. The slurry is cast onto a glass plate with a thickness of 130 μm and dried at room temperature for 24 h. Then, the temperature is raised to 60 °C and dried for 24 h to obtain a composite solid electrolyte with a thickness of 102 μm.
[0051] Example 2 It is basically the same as Example 1, except that in step S1, the mass ratio of talc, tannic acid and water is 1:0.01:400.
[0052] Example 3 It is basically the same as Example 1, except that in step S1, the mass ratio of talc, tannic acid and water is 1:0.03:400.
[0053] Example 4 It is basically the same as Example 1, except that in step S2, the mass ratio of lithium titanium phosphate to modified talc is 1:0.3.
[0054] Example 5 It is basically the same as Example 1, except that in step S2, the mass ratio of lithium titanium phosphate to modified talc is 1:0.5.
[0055] Example 6 The method is basically the same as in Example 1, except that the composite material consisting of lithium titanium phosphate and modified talc is 10 parts.
[0056] Example 7 The method is basically the same as in Example 1, except that the composite material consisting of lithium titanium phosphate and modified talc is 15 parts.
[0057] Example 8 The composite solid electrolyte in this embodiment, by mass fraction, comprises: 13 parts of a composite material consisting of lithium titanium phosphate and modified talc, 15 parts of LiODFP, and 20 parts of PVDF-HFP. The specific preparation method is as follows: S1. After dissolving tannic acid in water, add talc powder to obtain a reaction solution, wherein the mass ratio of talc powder, tannic acid and water is 1:0.02:500; stir the reaction solution at room temperature for 15 hours, then filter it, wash the filter residue with deionized water 3 times, and then dry it at 100℃ for 5 hours to obtain modified talc powder.
[0058] S2. The lithium titanium phosphate prepared in Preparation Example 1 and the modified talc powder were dispersed in ethanol at a mass ratio of 1:0.4, wherein the mass ratio of lithium titanium phosphate to ethanol was 1:5. After ball milling for 2 hours, the mixture was dried at 100°C for 18 hours to obtain a composite material composed of lithium titanium phosphate and modified talc powder.
[0059] The composite material consisting of S3, lithium titanium phosphate and modified talc, LiODFP and PVDF-HFP are dispersed in DMF solution, wherein the mass ratio of DMF to PVDF-HFP is 5:0.15. After uniform dispersion, a slurry is obtained. The slurry is cast onto a glass plate with a thickness of 110 μm and dried at room temperature for 18 h. Then, the temperature is raised to 50 °C and dried for 28 h to obtain a composite solid electrolyte with a thickness of 98 μm.
[0060] Example 9 The composite solid electrolyte in this embodiment comprises, by mass fraction, 12 parts of a composite material consisting of lithium titanium phosphate and modified talc, 15 parts of LiTFSI, and 20 parts of PVDF-CTFE. The specific preparation method is as follows: S1. After dissolving tannic acid in water, add talc powder to obtain a reaction solution, wherein the mass ratio of talc powder, tannic acid and water is 1:0.02:300; stir the reaction solution at room temperature for 10 hours, then filter it, wash the filter residue with deionized water 3 times, and then dry it at 120℃ for 3 hours to obtain modified talc powder.
[0061] S2. The lithium titanium phosphate prepared in Preparation Example 1 and the modified talc powder were dispersed in ethanol at a mass ratio of 1:0.4, wherein the mass ratio of lithium titanium phosphate to ethanol was 1:3. After ball milling for 3 hours, the mixture was dried at 120°C for 12 hours to obtain a composite material composed of lithium titanium phosphate and modified talc powder.
[0062] The composite material consisting of S3, lithium titanium phosphate and modified talc, LiTFSI and PVDF-CTFE were dispersed in DMF solution, wherein the mass ratio of DMF to PVDF-CTFE was 5:0.2. After uniform dispersion, a slurry was obtained. The slurry was cast onto a glass plate with a thickness of 140 μm and dried at room temperature for 28 h. Then, the temperature was raised to 70 °C and dried for 18 h to obtain a composite solid electrolyte with a thickness of 108 μm.
[0063] Electrochemical performance testing: (1) Ionic conductivity testing: The ionic conductivity of the composite solid electrolyte membranes prepared in Examples 1-9 and Comparative Examples 1-3 was tested using the following method. Stainless steel (Fe) was used as the blocking electrode, and Fe / solid electrolyte / Fe symmetric cells were assembled and impedance tests were performed. The ionic conductivity of the electrolyte was calculated according to the following formula: σ Where σ is the ionic conductivity, in S / cm; d is the thickness of the electrolyte sheet, in cm; R is the resistance of the Fe / electrolyte / Fe symmetric cell, in Ω; and S is the test area of the blocking electrode sheet, in cm². 2 The results of the ionic conductivity test are shown in Table 1.
[0064] (2) Cyclic performance test: LiNi 0.6 Co 0.2 Mn 0.2 O2, Super-P, and PVDF were mixed with NMP in a ratio of 8:1:1 to form a slurry. This slurry was then evenly coated onto aluminum foil using a 200μm doctor blade and baked in a vacuum oven at 100℃ for 2 hours before being cut into 12mm diameter circular electrode sheets. The electrolyte membrane was prepared using solid composite electrolyte membranes obtained in Examples 1-9 and Comparative Examples 1-3, cut into 16mm diameter circular sheets. The positive electrode used was a 12mm diameter ternary LiNi electrode. 0.6 Co 0.2 Mn 0.2O2 circular electrode sheets and a 14mm diameter lithium sheet as the negative electrode are used to assemble a sandwich-structure coin cell solid-state battery. The battery's cycle performance was tested as follows: Using a battery charge / discharge tester (model CT3002A) from Wuhan Landian Company, the assembled coin cell battery was subjected to two charge / discharge cycles at a rate of 0.1C, followed by a charge / discharge cycle test at a rate of 1C. The test temperature was 25℃, and the voltage range was 2.8~4.3V. The test results are shown in Table 2.
[0065] (3) The composite solid electrolyte membranes and lithium sheets prepared in Examples 1 and 1-3 were used to prepare Li-Li symmetric batteries, and the batteries were tested at 0.25 mA•cm. -2 The current density was measured, and electroplating / stripping cycles were performed at a test temperature of 25℃. The total charge and discharge time was 200 hours to test the cycle stability of the composite polymer solid electrolyte membrane and the lithium metal electrode. The test results are shown below. Figures 2-5 .
[0066] Table 1. Results of Ion Conductivity Tests As can be seen from the data in Table 1, the composite solid electrolyte prepared by pre-combining lithium titanium phosphate and tannic acid-modified talc in Example 1 has the highest ionic conductivity. In Comparative Example 1, without the addition of modified talc, the corresponding composite solid electrolyte has the lowest ionic conductivity, possibly due to the lack of synergistic effect from the tannic acid-modified talc, resulting in extremely low ion transport efficiency. In Comparative Example 2, using unmodified talc instead of modified talc, the ionic conductivity of the corresponding composite solid electrolyte is slightly higher than that of Comparative Example 1, but still significantly lower than that of Example 1. This may be because the surface of unmodified talc lacks polar groups such as phenolic hydroxyl groups, which cannot effectively promote lithium salt dissociation and anion fixation. In Comparative Example 3, lithium titanium phosphate and modified talc are added separately instead of pre-combined, resulting in a significantly higher ionic conductivity of the corresponding composite solid electrolyte than that of Comparative Example 1, but still significantly lower than that of Example 1. This may be because the two fillers cannot form an efficient "point-to-surface" ion transport network without prior ball milling and compounding. In Example 2, reducing the amount of tannic acid resulted in a decrease in the ionic conductivity of the prepared composite solid electrolyte compared to Example 1. This may be because insufficient tannic acid led to inadequate surface modification of the talc powder, resulting in a low density of phenolic hydroxyl groups. In Example 3, increasing the amount of tannic acid resulted in a slight decrease in the ionic conductivity of the prepared composite solid electrolyte compared to Example 1. This may be because excessive tannic acid formed an overly thick coating layer on the talc powder surface, partially hindering lithium-ion transport. In Example 4, reducing the mass ratio of lithium titanium phosphate to modified talc powder resulted in a decrease in the ionic conductivity of the prepared composite solid electrolyte compared to Example 1, indicating that insufficient interfacial activation occurred when the modified talc powder content was too low. In Example 5, increasing the mass ratio of lithium titanium phosphate to modified talc powder resulted in a slight decrease in the ionic conductivity of the prepared composite solid electrolyte compared to Example 1. This may be because an excessively high proportion of modified talc powder affected the construction of continuous conduction channels in lithium titanium phosphate, leading to a decrease in the ionic conductivity of the composite solid electrolyte. In Example 6, reducing the amount of composite material resulted in a decrease in the ionic conductivity of the prepared composite solid electrolyte compared to Example 1, indicating that insufficient composite material makes it difficult to construct a complete ion conduction network in the composite solid electrolyte. In Example 7, increasing the amount of composite material resulted in a decrease in the ionic conductivity of the prepared composite solid electrolyte compared to Example 1, possibly because excessive filler led to agglomeration, disrupting the continuous phase structure of the composite solid electrolyte. In Examples 8 and 9, adjusting the process parameters resulted in some fluctuation in the ionic conductivity of the prepared composite solid electrolytes, but overall, they all exhibited excellent ion conduction performance.
[0067] Table 2 As can be seen from the data in Table 2, the composite solid electrolyte prepared by pre-combining lithium titanium phosphate and tannic acid-modified talc in Example 1 exhibits superior initial specific capacity and capacity retention. In Comparative Example 1, without the addition of modified talc, the battery assembled from the prepared composite solid electrolyte shows poor initial specific capacity and cycle stability. This may be due to the lack of synergistic effect from the tannic acid-modified talc, resulting in extremely low ion transport efficiency and poor battery performance. In Comparative Example 2, using unmodified talc instead of modified talc, the battery assembled from the prepared composite solid electrolyte shows a slight improvement in initial specific capacity and cycle stability compared to Comparative Example 1, but is significantly inferior to Example 1. This may be because the surface of unmodified talc lacks polar groups such as phenolic hydroxyl groups, which cannot effectively promote lithium salt dissociation and anion fixation. In Comparative Example 3, lithium titanium phosphate and modified talc were added separately instead of pre-composite. The initial specific capacity and cycle stability of the battery assembled with the corresponding composite solid electrolyte were significantly improved compared to Comparative Example 1, but still significantly inferior to Example 1. This may be because the two fillers cannot form an efficient "point-to-surface" ion transport network without prior ball milling and compounding. In Example 2, reducing the amount of tannic acid resulted in a decrease in the initial specific capacity and cycle stability of the battery assembled with the corresponding composite solid electrolyte compared to Example 1. This may be because insufficient tannic acid led to inadequate surface modification of the talc and a low density of phenolic hydroxyl groups. In Example 3, increasing the amount of tannic acid resulted in a slight decrease in the initial specific capacity and cycle stability of the battery assembled with the corresponding composite solid electrolyte compared to Example 1. This may be because excessive tannic acid formed an overly thick coating layer on the talc surface, partially hindering lithium-ion transport. In Example 4, reducing the mass ratio of lithium titanium phosphate to modified talc resulted in a slight decrease in the initial specific capacity and cycle stability of the battery assembled with the corresponding composite solid electrolyte compared to Example 1. This may be because the proportion of modified talc was too low, resulting in insufficient interfacial activation performance. In Example 5, increasing the mass ratio of lithium titanium phosphate to modified talc resulted in a slight decrease in the initial specific capacity and cycle stability of the battery assembled with the prepared composite solid electrolyte compared to Example 1. This may be because the excessive proportion of modified talc led to a decrease in the continuity of ion conduction in the composite solid electrolyte. In Example 6, reducing the amount of composite material resulted in a decrease in the initial specific capacity and cycle stability of the battery assembled with the prepared composite solid electrolyte compared to Example 1, indicating that insufficient composite material makes it difficult to construct a complete ion conduction network in the composite solid electrolyte. In Example 7, increasing the amount of composite material resulted in a decrease in the initial specific capacity of the battery assembled with the prepared composite solid electrolyte compared to Example 1, and the cycle stability fluctuated slightly. This may be because excessive filler caused agglomeration, disrupting the continuous phase structure of the composite solid electrolyte.In Examples 8 and 9, the initial specific capacity and cycle stability of the batteries assembled with the corresponding composite solid electrolytes fluctuated to some extent when the process parameters were adjusted, but overall they all had better electrochemical performance, indicating that the composite material system has good tolerance to process parameters.
[0068] from Figures 2-5 It can be seen that the symmetric battery assembled with the composite solid electrolyte in Example 1 exhibits a stable lithium delithiation and lithium insertion process, with relatively stable voltage. The symmetric battery assembled with the corresponding composite solid electrolyte in Comparative Example 1 shows drastic voltage fluctuations after 170 hours, possibly due to lithium dendrite growth leading to micro-short circuits. The symmetric battery assembled with the composite solid electrolyte in Comparative Example 2 shows an increase in voltage after 170 hours, possibly due to an increase in internal resistance. The symmetric battery assembled with the composite solid electrolyte in Comparative Example 3 shows a smaller overall voltage variation and improved stability compared to Comparative Examples 1 and 2, indicating that the addition of the two fillers can exert a certain synergistic effect; however, its voltage plateau stability is still slightly inferior to that of Example 1. This may be because the two fillers, without prior ball milling and compounding, failed to form a highly efficient "point-to-surface" ion transport network as in Example 1, thus the overall performance was not optimal.
[0069] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A composite solid electrolyte, characterized in that, The composition, by mass fraction, includes: 10-15 parts of a composite material consisting of lithium titanium phosphate and modified talc, 15-30 parts of lithium salt, and 15-20 parts of polymer electrolyte; wherein: the modified talc is tannic acid modified talc; in the composite material consisting of lithium titanium phosphate and modified talc, the mass ratio of lithium titanium phosphate to modified talc is 1:(0.3-0.5).
2. The composite solid electrolyte according to claim 1, characterized in that, The preparation method of the composite material composed of lithium titanium phosphate and modified talc includes the following steps: ball milling and mixing lithium titanium phosphate and modified talc, followed by drying, to obtain the final product.
3. The composite solid electrolyte according to claim 2, characterized in that, The ball milling mixture is a wet ball milling mixture, and the medium for the wet ball milling mixture is ethanol; And / or, the ball milling mixing time is 2~3 hours; And / or, the drying temperature is 100~120℃, and the drying time is 12~18h; And / or, the mass ratio of lithium titanium phosphate to ethanol is 1:(3~5).
4. The composite solid electrolyte according to any one of claims 1 to 3, characterized in that, The method for preparing tannic acid-modified talc includes the following steps: adding tannic acid and talc into a solvent and stirring to react, thereby obtaining tannic acid-modified talc.
5. The composite solid electrolyte according to claim 4, characterized in that, The mass ratio of tannic acid to talc is (0.01~0.03):1; And / or, the mass ratio of talc powder to solvent is 1:(300~500), and the solvent is water; And / or, the stirring reaction time is 10-15 hours; And / or, after the stirring reaction is completed, the mixture is filtered, washed and dried in sequence to obtain tannic acid modified talc powder; wherein: the drying temperature is 100~120℃ and the drying time is 3~5h.
6. The composite solid electrolyte according to claim 1, characterized in that, The lithium salt is selected from one or more of lithium bis(oxalato)borate, lithium difluorooxalato)borate, lithium difluorobis(oxalato)phosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethyl)sulfonylimide, lithium tetrafluoroborate, and lithium hexafluorophosphate. And / or, the polymer electrolyte is selected from one or both of polyvinylidene fluoride-hexafluoropropylene copolymer and polyvinylidene fluoride-trifluorochloroethylene copolymer.
7. The method for preparing the composite solid electrolyte according to any one of claims 1 to 6, characterized in that, Includes the following steps: A composite material consisting of lithium titanium phosphate and modified talc, lithium salt, and polymer electrolyte are mixed and dispersed in a solvent to obtain a slurry. The slurry is then cast into a film and subjected to gradient drying to obtain a composite solid electrolyte.
8. The method for preparing the composite solid electrolyte according to claim 7, characterized in that, The solvent is one or both of N-methylpyrrolidone and N,N-dimethylformamide; And / or, the mass ratio of the polymer electrolyte to the solvent is (0.15~0.2):5; And / or, the thickness of the composite solid electrolyte is 90~110μm.
9. The method for preparing the composite solid electrolyte according to claim 7, characterized in that, The specific process of gradient drying is as follows: first, dry at room temperature for 18~28 hours, and then raise the temperature to 50~70℃ and dry for 18~28 hours.
10. A solid-state battery, characterized in that, Includes the composite solid electrolyte as described in any one of claims 1 to 6.
